The Relative Age Effect in Male and Female Brazilian Elite Volleyball Athletes of Varied Competitive Levels - de Oliveira Castro, Henrique; De Conti Teixeira Costa, Gustavo; Gomes, Sérgio Adriano; Júnior, Rubens Venditti [UNESP]; Tertuliano, Ivan Wallan; de Oliveira, Vivian [UNESP]; da Silva Aguiar, Samuel; Laporta, Lorenzo; Figueiredo, Lucas Savassi (SAGE Publications, 2023)
Volleyball is a popular sport in Brazil, and the relative age effect (RAE) is known to occur within it; but less is known of how RAE relates to elite Brazilian volleyball players’ age, sex, and competitive levels. We aimed to investigate RAE prevalence with data from two seasons of play among players in the Superliga A (2020/2021 and 2021/2022 seasons), and Superliga B (2021 and 2022 seasons) made available from the Brazilian Volleyball Confederation (CBV), the club’s official website, or direct consultation with the CBV. After removing duplicate data, we grouped these 1,063 athletes by their dates of birth, sex, and competition level (Superliga A or B). We divided players’ birth dates into quarters (Q1: January-March, Q2: April-June, Q3: July-September and Q4: October-December) and into semesters, and we performed chi-square (χ2) tests to investigate RAE prevalence according to the players’ sex and competitive level. RAE was prevalent overall (χ2 = 33.198; p <.001), among males (χ2 = 24.48; p <.001) and females (χ2 = 11.23; p <.011). Regarding competition level, RAE was evident among males in both Superliga A (χ2 = 14.581; p = 0.002), and B (χ2 = 13.985; p = 0.003), and among females in Superliga B (χ2 = 9.204; p = 0.027), but not Superliga A (χ2 = 4.012; p = 0.26). Thus, the RAE phenomenon operated differently for male and female Brazilian volleyball players according to their competitive level. We discuss the implications of these findings.
Keywords: age effect; athletes; female; male; team sports